Length Weight Relationship and Relative Condition Factor Study in Sahyadria chalakkudiensis Inhabiting Western Ghat River Systems of South India - Anju Pulapparambil; Mini Sekharan Nirichan; Harikrishnan Mahadevan; Sariga Palacode Karuppaswamy (Journal of Tropical Life Science, 2020)
A trend on unethical and unsustainable use of resources to meet the high demand in the trade of indigenous ornamental fishes is widespread. This increased exploitation calls for regulation. Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), an apex body having a central role in regulating the trade of any living organisms including indigenous ornamental fishes and preventing the species from being left as extinct. To enlist a species in trade by CITES, formulation of baseline data on its biology, population size, length-weight relations, condition factor, and habitat ecology are necessary. This paper looks into one such consideration on Sahyadria chalakkudiensis inhabiting Western Ghat rivers of Kerala. The length-weight relationships in respect of males and females inhabiting Chalakudy river are expressed as LogW = -3.800 + 2.43 LogL and LogW = -4.333 + 2.69 LogL while the same in males and females inhabiting Pooyamkutty river are LogW = -4.545 + 2.76 LogL and LogW = -5.290 + 3.12 LogL respectively .There is a regular seasonal cycle in relative condition factor with a peak in August (Kn=1.33; Chalakudy population) and September (Kn = 1.15; Pooyamkutty population).The results indicated that management of stock of S. chalakkudiensis is very essential to ensure sustainability of its trade.